A medium-range structure motif linking amorphous and crystalline states - Lan, Si; Zhu, Li; Wu, Zhenduo; Gu, Lin; Zhang, Qinghua; Kong, Huihui; Liu, Jizi; Song, Ruoyu; Liu, Sinan; Sha, Gang; Wang, Yingang; Liu, Qi; et al. (Nature materials, 2021)
Amorphous materials have no long-range order, but there are ordered structures at short range (2–5 Å), medium range (5–20 Å) and even longer length scales 1 – 5 . While regular 6 , 7 and semiregular polyhedra 8 – 10 are often found as short-range ordering in amorphous materials, the nature of medium-range order has remained elusive 11 – 14 . Consequently, it is difficult to determine whether there exists any structural link at medium range or longer length scales between the amorphous material and its crystalline counterparts. Moreover, an amorphous material often crystallizes into a phase of different composition 15 , with very different underlying structural building blocks, further compounding the issue. Here, we capture an intermediate crystalline cubic phase in a Pd-Ni-P amorphous alloy and reveal the structure of the medium-range order, a six-membered tricapped trigonal prism cluster (6M-TTP) with a length scale of 12.5 Å. We find that the 6M-TTP can pack periodically to several tens of nanometres to form the cube phase. Our experimental observations provide evidence of a structural link between the amorphous and crystalline phases in a Pd-Ni-P alloy at the medium-range length scale and suggest that it is the connectivity of the 6M-TTP clusters that distinguishes the crystalline and amorphous phases. These findings will shed light on the structure of amorphous materials at extended length scales beyond that of short-range order. An intermediate cube phase with a medium-range order structure is identified in Pd-Ni-P metallic glass, which links the amorphous and crystalline phases.